Novel elastic, lattice dynamics and thermodynamic properties of metallic single-layer transition metal phosphides: 2H-M2P (Mo2P, W2P, Nb2P and Ta2P). (2nd March 2018) - Yin, Jiuren; Wu, Bozhao; Wang, Yanggang; Li, Zhimi; Yao, Yuanpeng; Jiang, Yong; Ding, Yanhuai; Xu, Fu; Zhang, Ping
Abstract: Recently, there has been a surge of interest in the research of two-dimensional (2D) phosphides due to their unique physical properties and wide applications. Transition metal phosphides 2H- M 2 Ps (Mo2 P, W2 P, Nb2 P and Ta2 P) show considerable catalytic activity and energy storage potential. However, the electronic structure and mechanical properties of 2D 2H- M 2 Ps are still unrevealed. Here, first-principles calculations are employed to investigate the lattice dynamics, elasticity and thermodynamic properties of 2H- M 2 Ps. Results show that M 2 Ps with lower stiffness exhibit remarkable lateral deformation under unidirectional loads. Due to the largest average Grüneisen parameter, single-layer Nb2 P has the strongest anharmonic vibrations, resulting in the highest thermal expansion coefficient. The lattice thermal conductivities of Ta2 P, W2 P and Nb2 P contradict classical theory, which would predict a smaller thermal conductivity due to the much heavier atom mass. Moreover, the calculations also demonstrate that the thermal conductivity of Ta2 P is the highest as well as the lowest thermal expansion, owing to its weak anharmonic phonon scattering and the lowest average Grüneisen parameter. The insight provided by this study may be useful for future experimental and theoretical studies concerning 2D transition metal phosphide materials.